Factors affecting the length of hospital stay in adult patients with alcohol dependence - Geniş, Bahadır; Coşar, Behçet; Arıkan, Zehra (Journal of Dependence, 2020)
Objective: The aim of this study was to investigate the causes of long hospital stay in adult patients with alcohol use disorder inpatient treatment.Method: The study included the records of patients treated in the alcohol and drug addiction clinic of Gazi University Hospital between 2005 and 2016. The records of 1543 patients with alcohol dependence were reached. Only the first hospitalization data of patients with recurrent admission were included in the analysis. As a total the records of 906 patients were analyzed.Results: The mean age of the study population was 51.95±11.54 years and 89.4% (n = 810) were male. Recurrent hospitalization was 26.7% (n = 242), medical comorbidity 5% (n = 45), and psychiatric comorbidity 28% (n = 254). In the logistic regression analysis evaluating the duration of hospitalization, the presence of bipolar affective disorder (BDD) increased the duration of hospitalization by 3.4 times (OR=3.457), and the presence of depression extended the duration of hospitalization by 1.8 times (OR=1.854). The length of hospital stay of those hospitalized between 2014-2016 was 12 times (OR=0.082) shorter than those hospitalized between 2005-2007.Conclusion: Some clinical variables (age, BDD and depression) have been shown to affect the duration of hospitalization in alcohol dependence. Together with these clinical variables, a non-clinical variable, such as the year of hospitalization, was found to affect the length of hospital stay 12-fold. Moreover, this effect can increase up to 34 times.
Keywords: Alcohol dependence; length of stay; alcohol use disorder; depression